HBV, HCV, and HDV Triple-Infection—A Therapeutic Challenge - Alexia Anastasia Stefania Balta; Mariana Daniela Ignat; Raisa Eloise Barbu; Liliana Baroiu; Lavinia Alexandra Moroianu; Valerii Lutenco; Valentin Bulza; Mihaela Patriciu; Caterina Dumitru; Mihaela Debita (Diseases)
Purpose: This article aims to harmonize the current data from the literature, describe baseline severity, and discuss potential treatment considerations for cases of triple infection. Patients and Methods: We undertook a retrospective, observational study on 1244 patients with viral hepatitis study subgroups: chronic replicative hepatitis with HCV—679 patients, HBV—98 patients, HBV/HCV—25 patients, HBV/HDV—14 patients, and 2 patients with triple-infection (HBV, HCV, and HDV), hospitalized in the Second Department of “Sf. Cuv. Parascheva” Infectious Diseases Clinical Hospital of Galați, Romania, between 1 April 2017 and 1 March 2025. Results: Comparative analysis of biochemical parameters and liver fibrosis—at the initial testing—i.e., at the beginning of the specific antiviral therapy—with direct-acting antivirals on HCV (DAAs) or nucleos(t)ide analogues (NUCs): Entecavir (ETV) or Tenofovir Disoproxyl fumarate (TDF), for HBV, Bulevirtide (BLV) for HDV—revealed clinical forms with higher severity in the case of triple and double infections, in comparison to individuals who have had only one hepatotropic virus infection. Conclusions: Compared to patients with a single hepatotropic viral infection, those with a double or triple infection had more severe hepatic damage. Concomitant therapy with Bulevirtide, DAAs, and NUCs is possible and the therapeutic results from clinical studies, with single-infection patients showing great potential for improving the prognosis of these patients.